(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study aimed to analyze the effects of the use of binders on the physical quality and digestibility of Alabio ducks (Anas platyrinchos Borneo). Materials and Methods: Pellet binders used tapioca meal (TM) (Manihot utilissima), sago meal (SM) (Metroxylon sagu Rottb.), and sweet potato meal (SPM) (Ipomoea batatas) pelleted feed. Laying Alabio ducks, around 120 birds, aged 20 weeks with an average body weight of 1,426 ± 113.5 gm, were used. A fully randomized design with 4 treatments and 15 repeats was used in this study. The variables measured include the physical quality and digestibility of pellet feed. Data analysis used a Fisher test. For the distinction between treatments, the Duncan multiple-range test was conducted. Results: The finding showed that the plant-based pellet binder had a natural effect on physical properties, including pellet durability index, moisture content, threshold power, stack density, and stack compacted density. The strength of the pellet binder is seen in the durability index of TM 98.12%, SM 97.64%, and SPM 97.35%, respectively. However, these variables did not differ significantly in terms of specific gravity and stack angle. Pellet binders considerably affect the consumption of feed and vary markedly in dry matter, organic matter, and metabolizable energy digestibility. Conclusion: Plant-based pellet binders influence the physical quality and digestibility of pelleted feed in Alabio ducks. TM can maintain physical quality and digestibility compared to SM and SPM as plant-based pellet binders. Adv. Vet. Anim. Res., 11(1): 93-99, March 2024 http://doi.org/10.5455/javar.2024.k752